ENFORCEMENT OF LAW ON CONSUMER PROTECTION TO INCREASE THE VALUE OF JUSTICE - Nainggolan, Ibrahim; Koto, Ismail; Simatupang, Rajarif Syah Akbar (NOMOI Law Review, 2023)
The problems faced by society are not only related to the choice of goods, but are much more complex and involve the perception of all parties, both business actors and consumers, regarding the importance of consumer protection. Consumer protection law or consumer law can be understood as all legal provisions that regulate the rights and obligations of consumers and producers arising from efforts to fulfill their needs. The word comprehensive is intended to describe that it covers all differences in law according to its type. This research is normative legal research, namely legal research that places law as a building system of norms. Normative legal research is law that is conceptualized in terms of norms or rules that apply in society. In regulating consumer protection legal regulations in fulfilling the value of justice in Indonesia today optimally and providing opportunities for consumers and economic actors to achieve their rights and fulfill their obligations equally.